1980
DOI: 10.1007/bf02115942
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behavior of assailants during reported rapes

Abstract: The present study reports on the forced sexual, excretory, and sadistic acts that occur during rape. The main sample consisted of 115 adult, adolescent, and child rape victims that were admitted during a 1-year period to the emergency wards of a large municipal hospital. Forced vaginal intercourse was the most frequent act reported, but many other acts also occurred, ranging from fellatio and cunnilingus to urinating on the victim. It is argued that various social-psychological meanings are attached to forced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1
4

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 5 publications
2
24
1
4
Order By: Relevance
“…They either clustered together or were positioned in a pattern within each of the corresponding perceptual maps, and statistical analysis indicated a good fit or a good explanation for the data. The characteristics associated with each of these types were generally consistent with those proposed by other researchers (e.g., Holmstrom & Burgess, 1980;Knight & Prentky, 1990;Prentky & Knight, 1991). However, not all of the characteristics associated with each of the four types were located within these clusters or patterns, which suggested that some characteristics may not fit with the proposed types.…”
Section: Discussionsupporting
confidence: 69%
“…They either clustered together or were positioned in a pattern within each of the corresponding perceptual maps, and statistical analysis indicated a good fit or a good explanation for the data. The characteristics associated with each of these types were generally consistent with those proposed by other researchers (e.g., Holmstrom & Burgess, 1980;Knight & Prentky, 1990;Prentky & Knight, 1991). However, not all of the characteristics associated with each of the four types were located within these clusters or patterns, which suggested that some characteristics may not fit with the proposed types.…”
Section: Discussionsupporting
confidence: 69%
“…Theories of group dynamics may, therefore, offer explanations for hostile behaviours in group rape, suggesting for example, feelings of male camaraderie (Holmstrom & Burgess, 1980), where offenders are not only interacting with the victim but also members of their own group. Likewise, Bijleveld et al (2007) studied group rape suggesting that rivalry within the group, striving for performance and an element of entertainment all play a role in the behaviours displayed in group rape.…”
Section: Discussionmentioning
confidence: 98%
“…Group dynamics including peer pressure, groupthink, cohesiveness and modelling (Porter & Alison, 2005;Woodhams, Gillett, & Grant, 2007) have all been suggested to contribute to the nature of group interaction in sexual assault. Researchers have also outlined group rape to be primarily motivated by comradeship and male camaraderie (Groth & Birnbaum, 1980: Holmstrom & Burgess, 1980, an element of excitement, 'kick', or adventure (Scully & Marolla, 1985). Further, there is a view that group rape occurs in the context of violence rather than passion (Hilberman, 1976).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies have shown that the attackers acting as a group, compared to those who act alone, differ with respect to cooperation. Group aggressors, in fact, show "affectionate" behaviors more frequently, such as kissing, caressing and gently undressing the victim, to make her "work" (Holmstrom & Burgess, 1980). Alison and Stein found that submissive behavior by the aggressor is not common.…”
Section: Sociological and Scientific Profiles Of Individual And Groupmentioning
confidence: 99%